PENERAPAN STRATEGI BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA KARYAWAN PUSKESMAS BANGKINGAN SURABAYA - Rani, Novi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the performance assessment of Puskesmas Bangkingan, Surabaya when it is measured by using Balanced Scorecard method which considers the four perspectives i.e.: financial perspective, customer perspective, internal business process perspective, and growth and learning perspective.The result of research shows that the performance assessment that has been carried out by using Balanced Scorecard method at Puskesmas Bangkingan, Surabaya can be concluded that there is an enhancement of income and the realization of budget that can be processed efficiently shows good financial performance, the customer perspectives which consist of customer satisfaction, customer loyalty and number of complaint have already run well, the internal business perspective the service and innovation that has been made by the Puskemas Bangkingan Surabaya has already run well, it can be proved from new medical equipments in order to make medical services more convenience, and the growth and learning perspective shows that community health clinic can keep the number of its employees, improve its employeesâ productivity, and improve employeesâ service quality by holding trainings.Keywords: Balanced Scorecard, Growth and Learning Perspective, Internal Business Process Perspective, Customer Perspective, Financial Perspective.